2007
DOI: 10.1093/jxb/erm267
|View full text |Cite
|
Sign up to set email alerts
|

Dual targeting of the tRNA nucleotidyltransferase in plants: not just the signal

Abstract: Enzymes involved in tRNA maturation are essential for cytosolic, mitochondrial, and plastid protein synthesis and are therefore localized to these different compartments of the cell. Interestingly, only one isoform of tRNA nucleotidyltransferase (responsible for adding the 3'-terminal cytidine-cytidine-adenosine to tRNAs) has been identified in plants. The present study therefore explored how signals contained on this enzyme allow it to be distributed among the different cell compartments. It is demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…We also demonstrated that the different start codons within the TSPO N-terminal extension could target the TSPO protein to different organelles. Other plant proteins such as MDAR (Arabidopsis Monodehydroascorbate Reductase) and tRNA nucleotidyltransferase [44,45] are also known to be targeted to different organelles owing to alternative transcriptionsal start sites. Thus, it is tempting to speculate that, cloroplastic At TSPO may protect the chloroplast from salt stress damage and the mitochondrial At TSPO may normally import chloroplast-synthesized porphyrins into the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that the different start codons within the TSPO N-terminal extension could target the TSPO protein to different organelles. Other plant proteins such as MDAR (Arabidopsis Monodehydroascorbate Reductase) and tRNA nucleotidyltransferase [44,45] are also known to be targeted to different organelles owing to alternative transcriptionsal start sites. Thus, it is tempting to speculate that, cloroplastic At TSPO may protect the chloroplast from salt stress damage and the mitochondrial At TSPO may normally import chloroplast-synthesized porphyrins into the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…To further generalize our findings, proteins with either similar destinations or distinct or unknown targeting routes were selected, i.e. the essential nuclear protein 1 (Enp1; nucleus; Missbach et al, 2013), the a-helical outer envelope protein of 7 kDa (OEP7; chloroplast; Machettira et al, 2011), the precursor of the vesicle-inducing protein in plastids 1 (pVipp1; chloroplast; Kroll et al, 2001), the b-barrel-shaped outer membrane protein of 24 kDa (OEP24; chloroplast; Pohlmeyer et al, 1998), the dual-targeted tRNA nucleotidyltransferase (tRNA-NT; mitochondria, chloroplast, nucleus; Schmidt von Braun et al, 2007), and Nob1 (cytosol; Missbach et al, 2013). The abundance of Enp1-GFP, Nob1-GFP, OEP7-GFP, and pVipp1-GFP was not affected by alterations of the Hsp70 or Hsp90 chaperone levels, irrespective of the construct used for co-transformation ( Figure 6 and Supplemental Figure 9).…”
Section: The Role Of Transit Peptides In Hsp90-dependent Protein Abunmentioning
confidence: 99%
“…We hope that CyMIRA will serve as useful community resource in this respect. (Hooper, et al 2017) eSLDB 848 4427 69 (Pierleoni, et al 2007) PA-GOSUB 985 730 14 (Lu, et al 2005) SUBA experimental 1217 2128 785 (Hooper, et al 2017) SWISS PROT 311 657 20 (Boutet, et al 2007) TAIR 397 1598 266 (Reiser, et al 2017) LocDB 446 1527 234 (Rastogi and Rost 2011) PPDB 327 1570 73 (Sun, et al 2009) Organelle DB 512 276 11 (Wiwatwattana, et al 2007) Kurisu et al 2003;Friso et al 2004;Nelson et al 2004;Jensen et al 2007;Izumi et al 2012;Shikanai 2016;Bezouwen et al 2017;Laughlin et al 2019PPR Lurin et al 2004Toole et al 2008;Fujii et al 2010;Cheng et al 2016 Transcription and transcript maturation Hess and Borner 1999;Walter et al 2002;Gu et al 2003;Perrin et al 2004;Kuhn et al 2007;Schmidt von Braun et al 2007;Yu et al 2008;Canino et al 2009;Delannoy et al 2009;Chen et al 2010;Falcon de Longevialle et al 2010;Gobert et al 2010;Placido et al 2010;Richter et al 2010;Babiychuk et al 2011;Bryant et al 2011;Gerdes et al 2011;Sharwood et al 2011;Apitz et al 2014;…”
Section: Resultsmentioning
confidence: 99%